Measurement based modeling and validation of wireless MIMO channel models - A. A. Kalachikov; N. S. Shelkunov (Омский научный вестник)
This paper addresses measurement based wireless MIMO channel modeling and validation based MIMO channel on sounding data. Measurement is carried out in indoor laboratory environment at central frequency 2,3 GHz with measurement bandwidth 100 MHz, 4 transmit and 4 receive antennas are used. Obtained impulse responses are presented and used for channel parameters estimation. Measured channel capacity CDF curves are presented. Full channel correlation matrix is calculated, showing spatial correlation. For statistical analysis estimation of distribution of channel coefficients and goodness of fit tests are numerically computed. Correlated channel capacity compared with uncorrelated channel is presented. Correlation-based models describe the (complex) correlation properties between all pairs of receive and transmit antennas. Two analytical MIMO channel models — Kronecker and Weichselberger models are evaluated.